A Wideband Vivaldi Array With Enhanced Power Handling Capacity - Hongzhou Gong; Jiande Zhang; Chengwei Yuan; Qiang Zhang; Yanhong Yu (International Journal of Antennas and Propagation, 2025)
This paper proposes an all-metal Vivaldi array based on the tight coupling effect with enhanced power handling capacity (PHC). To achieve this, L29 connectors and enlarged parallel-plate waveguides are strategically implemented to reduce localized electric field intensity. By optimizing the reflective cavity dimensions, half-wavelength resonance within the operational bandwidth is effectively suppressed. Furthermore, extending the arms of edge elements mitigates the E-plane truncation effect. The designed array demonstrates an active voltage standing wave ratio (VSWR) below 2 across 0.55–4.17 GHz and below 3 within 0.53–4.15 GHz while scanning up to 45° in both E- and H-planes. A prototype 8 × 10 array (370 × 240 mm) was fabricated and tested, achieving a PHC of ≥ 10.1 MW at broadside and ≥ 7.25 MW at 45° scan angles. Measured results align closely with simulations, validating the design’s robustness for high-power microwave (HPM) applications.